Some Information About the Names of The Mosque Located in Margilan (Zien Journal of Social Sciences and Humanities, 2021)
This article provides a brief overview of the science of toponymy, the names of some mosques in the city of Margilan, Fergana region, as well as the views of scholars on the toponym Kirguli.